Odpowiedzi

2009-11-24T18:56:43+01:00
A) (x + 4) + (2x - 6) =x+4+2x-6=3x-2
b) -(2y + 3x) + (-4y + 2x + 1) =-2y-3x-4y+2x+1=-6y-x+1
c) -(x - 2xy) - (4x + xy) + (xy - x) =-x+2xy-4x-xy+xy-x=-6x+2xy
d) (x² + 2x + 1) - (x² - 4x + 3) =x²+2x+1-x²+4x-3=6x-2

Pozdro:)
Najlepsza Odpowiedź!
2009-11-24T19:06:14+01:00
A) (x + 4) + (2x - 6) =x+4+2x-6=3x-2
b) -(2y + 3x) + (-4y + 2x + 1) = -2y -3x -4y +2x +1= -6y -x +1
c) -(x - 2xy) - (4x + xy) + (xy - x) = -x +2xy -4x -xy +xy -x= -6x +2xy
d) (x² + 2x + 1) - (x² - 4x + 3) = x²+2x+1-x²+4x-3=6x-2